2006
DOI: 10.1093/qjmam/hbj004
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic scattering from an anisotropic impedance half-plane at oblique incidence: the exact solution

Abstract: SummaryScattering of a plane electromagnetic wave from an anisotropic impedance half-plane at skew incidence is considered. The two matrix surface impedances involved are assumed to be complex and different. The problem is solved in closed form. The boundary-value problem reduces to a system of two first-order difference equations with periodic coefficients subject to a symmetry condition. The main idea of the method developed is to convert the system of difference equations into a scalar Riemann-Hilbert probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…This is a homogeneous problem "adjoint" to problem (2), and its solutions are searched for in a so-called "adjoint" class. Its solution can be constructed in the same way as a solution of homogeneous problem (12).…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a homogeneous problem "adjoint" to problem (2), and its solutions are searched for in a so-called "adjoint" class. Its solution can be constructed in the same way as a solution of homogeneous problem (12).…”
Section: Definitionmentioning
confidence: 99%
“…., dw h (p) is a basis of Abelian differentials of the first kind. If the right-hand side of (77) is multiple of the integer divisor (dΨ0) J D , then from (77) we can obtain a particular solution of non-homogeneous problem (2). This leads to a system of linear equations for finding the numbers c 1 , .…”
Section: Theorem 4 Non-homogeneous Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution to the classical inversion problem (4.27) always exists [18] and can be expressed through the M zeros of the associated Riemann theta-function of the surface R [1][2][3]. Notice that since (4.29) does not depend on the integers n ν , they can be chosen arbitrarily say, n 1 = · · · = n M = 0, provided the points q ν and the integers m ν solve the problem (4.27).…”
Section: J=1mentioning
confidence: 99%
“…Furthermore, just like the Wiener‐Hopf technique, which was regarded for many decades as not being suitable for wedge problems but now has outperformed the Sommerfeld‐Malyuzhinets technique in certain aspects, the Sommerfeld‐Malyuzhinets technique could one day get the upper hand again. In addition, a closed‐form explicit solution to the problem under study ought to be found yet (for such solutions in special cases see, for instance, Lyalinov and Zhu [1999, 2003a] and Antipov and Silvestrov [2006]). Hence this solution procedure deserves to be presented to the electromagnetics community.…”
Section: Introductionmentioning
confidence: 99%